Environmental Geostrategic Analysis in the Development of the Archipelago's Capital City - Theresia Evelyn; Sabiyan Arafi; Nathan Aristiphano; Nashita Saaliha; Aurennisa Nindia Eka Putri; Beatrice Andreanna Wijaya (CV. Rayyan Dwi Bharata, 2022)
The development of the National Capital City (IKN) of the Archipelago is faced with major ecological challenges, both because of the existing conditions of Penajam Paser Utara Regency and Kutai Kartanegara Regency and because of the vision of IKN which is green and sustainable. This study aims to analyze the Government's strategy in managing environmental resources and solving existing ecological problems in accordance with the IKN's vision. The research was conducted qualitatively through literature studies from various sources, including academic texts, laws, articles, journals and press conferences from government agencies. It was found that the Government has made various efforts to realize the vision of the IKN and protect the environment such as seeking raw and clean water supplies, managing land, and reclaiming ex-mining pits. But it takes enormous resources to do so, along with good execution, monitoring and evaluation.